Survivability under Overheating The impact of Regional and Global Climate Change on Vulnerable and Low Income Population - Synnefa, Afroditi; Haddad, Shamila; Rajagopalan, Priya; Santamouris, Matthaios (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The present book discusses three significant challenges of the built environment, namely regional and global climate change, vulnerability, and survivability under the changing climate. Synergies between local climate change, energy consumption of buildings and energy poverty, and health risks highlight the necessity to develop mitigation strategies to counterbalance overheating impacts. The studies presented here assess the underlying issues related to urban overheating. Further, the impacts of temperature extremes on the low-income population and increased morbidity and mortality have been discussed. The increasing intensity, duration, and frequency of heatwaves due to human-caused climate change is shown to affect underserved populations. Thus, housing policies on resident exposure to intra-urban heat have been assessed. Finally, opportunities to mitigate urban overheating have been proposed and discussed.